A deployment model of EV charging piles and its impact on EV promotion. (November 2020) - Ma, Shao-Chao; Fan, Ying
Abstract: The construction of public-access electric vehicle charging piles is an important way for governments to promote electric vehicle adoption. The endogenous relationships among EVs, EV charging piles, and public attention are investigated via a panel vector autoregression model in this study to discover the current development rules and policy implications from the historical panel data in China. Five policies related to EV charging piles, EV purchase subsidies, commercial land prices, and retail gasoline prices are controlled as exogenous variables in the model. The results indicate that EV and charging piles diffusion do interact, and public attention plays a nexus role in EV and charging piles deployment. Reducing the electricity rate is the most effective policy approach to promote EV charging piles. Subsidising the construction cost has an insignificant impact on charging piles diffusion in this study, and several possible reasons have been discussed. The promotion effect of direct-current charging piles on EV sales is twice that of alternating-current charging piles in the one-year simulation of our model. Increasing the number of EV charging piles has a significant impact on battery electric vehicle sales but not on plug-in hybrid electric vehicle sales. Highlights: There is an interaction between EV sales and the number of public EVCPs. Building DC charging piles has twice the impact on EVs sales as building AC piles. The number of EVCPs has a significant impact on BEV sales. Public attention is an important nexus in promoting the deployment of EVCPs. Discounts on electricity bills are the most effective policy to promote EVCPs.